HDAC6 Regulates the Fusion of Autophagosome and Lysosome to Involve in Odontoblast Differentiation - Zhan, Yunyan; Wang, Haisheng; Zhang, Lu; Pei, Fei; Chen, Zhi (Frontiers in Cell and Developmental Biology, 2020)
Odontoblast differentiation is an important process during tooth development in which pre-odontoblasts undergo elongation, polarization, and finally become mature secretory odontoblasts. Many factors have been found to regulate the process, and our previous studies demonstrated that autophagy plays an important role in tooth development and promotes odontoblastic differentiation in an inflammatory environment. However, it remains unclear how autophagy is modulated during odontoblast differentiation. In this study, we found that HDAC6 was involved in odontoblast differentiation. The odontoblastic differentiation capacity of human dental papilla cells was impaired upon HDAC6 inhibition. Moreover, we found that HDAC6 and autophagy exhibited similar expression patterns during odontoblast differentiation both in vivo and in vitro; the expression of HDAC6 and the autophagy related proteins ATG5 and LC3 increased as differentiation progressed. Upon knockdown of HDAC6, LC3 puncta were increased in cytoplasm and the autophagy substrate P62 was also increased, suggesting that autophagic flux was affected in human dental papilla cells. Next, we determined the mechanism during odontoblastic differentiation and found that the HDAC6 substrate acetylated-Tubulin was up-regulated when HDAC6 was knocked down, and LAMP2, LC3, and P62 protein levels were increased; however, the levels of ATG5 and Beclin1 showed no obvious change. Autophagosomes accumulated while the number of autolysosomes was decreased as determined by mRFP-GFP-LC3 plasmid labeling. This suggested that the fusion between autophagosomes and lysosomes was blocked, thus affecting the autophagic process during odontoblast differentiation. In conclusion, HDAC6 regulates the fusion of autophagosomes and lysosomes during odontoblast differentiation. When HDAC6 is inhibited, autophagosomes can't fuse with lysosomes, autophagy activity is decreased, and it leads to down-regulation of odontoblastic differentiation capacity. This provides a new perspective on the role of autophagy in odontoblast differentiation.